The Relationship between Personnel Behavior and Work Effectiveness with the Ability to Adapt to Disruptive Situations as Mediation - Warganegara, Ariefaldi; Adam, Mohammad; Zunaidah,; Yuliani, (Jurnal Manajemen, 2024)
This research aims to investigate the relationship between personnel behavior and the job effectiveness of Bhabinkamtibmas (Non-Commissioned Officers responsible for Community Security and Order Maintenance) with adaptability as a mediating variable in disruptive situations. The research methodology involved 310 samples out of a total of 1369 Bhabinkamtibmas personnel distributed within the research area. The research findings indicate that personnel behavior does not have a direct significant influence on job effectiveness. However, an interesting finding is the presence of a positive and significant influence between personnel behavior and adaptability. Furthermore, adaptability has a positive and significant influence on the job effectiveness of Bhabinkamtibmas. Mediation analysis reveals that adaptability acts as a partial mediator in the relationship between personnel behavior and job effectiveness. This research significantly contributes to understanding the factors affecting the job effectiveness of Bhabinkamtibmas in the midst of disruptive situations. Research recommendations encompass the need to enhance training and development focusing on improving the adaptability of Bhabinkamtibmas personnel, as well as the implementation of effective behavioral management strategies in their work context. Thus, the results of this research have practical implications for enhancing the quality of security and community order services provided by Bhabinkamtibmas in the face of dynamic and challenging situations.